Optimasi Operasi Pembangkit Listrik Tenaga Air (PLTA) Menggunakan Linear Programming Dengan Batasan Ketersediaan Air - Winasis Winasis; Hari Prasetijo; Giri Angga Setia (Jenderal Soedirman University, 2013)
One of hydro power plant operational problem is how to maximize available water resouces to gather optimal electric power generation. Water availability which is limited and can be stored in a reservoir will influence electrical energy generated by the plant. This paper present a new approach of short term optimization of hydro power plant operation. The objective function is to maximize energy which is produced by power plant on scheduling operation period, with consider water resource availability in reservoir as operational constraint. The optimization problem is formulated in Linear Programming Method, in which this method is a commonly used to solve optimization problem in hydro power plant. Based on simulation results on Ketenger Hydro Power Plant using water flow data on June 1st 2013 shows that this method can be used to solve hydro power plant operation optimization problem well. Electrical energy as main objective function is maximized and all prevailing constrain is satisfied. On this short term operation (24 hour) simulation, total energy can be produced is 96121,55 kWh, or 1427 kWh (1,51%) greater comparing with real generation condition with 96694 kWh.